Transport outsourcing and transport collaboration relationship - the risk hedging perspective - Stojanović, Đurđica M.; Aas, Bjørnar (Serbian Journal of Management, 2015)
Although transport outsourcing decision-making and collaborative transport management (CTM) have been “hot topics” for years, their links are still not thoroughly explored. The purpose of this paper is to contribute to a better understanding of the relationship between them. In particular, we focus on the conflicting and complementary features of these concepts with regard to their capability to hedge against transport outsourcing-related risks. Transport outsourcing is often a tool for transferring part of the demand risks from the primary parties in supply chains to transport service providers. However, new relationships introduce some new risks - outsourcing contract risks. It is important to identify, estimate and compare such kinds of risks. Transport collaboration may decrease both the demand risks and the outsourcing contract risks, although the relationship with the latter is more complex. It is used an exploratory research based on a combination of a literature review and empirical examples.